PENGARUH LATIHAN SPRINT 30 METER TERHADAP KECEPATAN LARI PADA PEMAIN SEPAKBOLA DI SSB PEKANBARU CITY SOCCER SCHOOL - Muhammad Rayhan; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted to find out whether there is any influence of 30 meter sprint exercise on running speed on soccer player at SSB Pekanbaru City Soccer School. The form of this research is research with experimental treatment (experiment), with 64B student population of SSB, sampling is done by purposive sampling, in this study the sample is SSB U-15 students with total 16 people. Instrument performed in this research is a 50-yard sprint test, which aims to measure the speed. After that the data in though with statistics, to test the normality with liliefors test at a significant level of 0.05a. The hypothesis proposed is the effect of 30 meter sprint exercise on speed. Based on T test analysis yield T count equal to 6,380 and T table equal to 1,753, mean T count> T table. Based on the statistical data analysis, there is an average pree test of 6.98 and the average post test of 6.83 then the data is normal. From the description can be concluded that there is the influence of Sprint Training 30 meters against the speed of running on football players SSB Pekanbaru City Soccer SchoolKeywords: Sprint 30 meters, Speed